Flood in housing projects in Malaysia: A planning law perspective (Part 3) - Md Dahlan, Nuarrual Hilal (2021)
Flood in housing projects is typical in Malaysia, particularly during monsoon and tropical wet seasons. There are various causes to it. These include heavy monsoon rain, flawed drainage system, insufficient planning system, inadequate flood risk management strategy, exorbitant rainfall, rapid melting snow and ice, dams or levees breaking, ocean storm surge and sea level rising. The catastrophe has resulted in pecuniary and non-pecuniary losses to the purchaser residents. Flood is one of the important matters that developers must address during the development planning stage. The developer should get views and approvals from relevant technical agencies, including the agencies responsible for governing safety and security against flood disasters, for instance, the Department of Irrigation and Canal (JPS). This paper aims to study flood legal issues and examine the planning law relating to floods in housing projects. It also provides suggestions for improving the current planning law in dealing with this catastrophe. This paper uses legal research methodology and qualitative research methodology, particularly concerning eliciting information through available literature to study the problem. The instant paper is the Part 3, as do Part 1 and Part 2, in discussing the planning issues and planning legal aspects relating to the occurrences of flood disasters in housing development. In continuation of Part 1 and Part 2, this Part 3 instant paper likewise finds that there are lacunae in the planning law that have contributed to flooding occurrences in housing projects. Certain suggestions are provided in the ending part of this paper to deal with the flood problem. Similarly, this Part 2 instant paper, finds that there are lacunae in the planning law that have contributed to flooding occurrences in housing projects. Certain suggestions are provided in the ending part of this paper to deal with the flood problem. The outcome of Part 1, Part 2 and Part 3's writings, it is submitted, can improve the current policy and planning law in housing development, particularly the housing development guidelines and the current National Housing Policy (DPN) (2018-2025).